Bayesian Statistical Methods and Their Valuable Applications in the Pharmaceutical Sciences - Farzan MADADIZADEH; Mohammad EZATI ASAR; Mostafa HOSSEINI (Tehran University of Medical Sciences, 2016)
Bayesian Statistical Methods and Their Valuable Applications in the Pharmaceutical Sciences